Komparasi Pemahaman Konsep Matematika Siswa Melalui Penerapan Model Pembelajaran Auditory Intellectually Repetition (AIR) dan Model Pembelajaran Reciprocal Teaching (RT) - Talib, Ahmad; Ihsan, Hisyam; Fairul, Muh. (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
The research applied quasi-experimental design involving two groups that received treatment. The objective of the research was to find out the comparison of mathematics concept understanding between students who were taught by using Auditory Intellectually Repetition (AIR) and Reciprocal Teaching (RT) Learning Method. The sample of the research consisted of two classes who were decided by cluster random sampling technique. The data were collected through the ability of students’ mathematics concept understanding instrument test and observation. The result of the research showed that 1) The learning process by using Auditory Intellectually Repetition (AIR) learning method was better to be applied in the VIII class of junior high school (SMPN) in Barru district 2) The students’ understanding of mathematics concepts that was taught by using Auditory Intellectually Repetition (AIR) was better than their understanding of mathematics concept that was taught by Reciprocal Teaching (RT) in learning Mathematics in the VIII class of junior high school (SMPN) in Barru district.